Estimating households’ marginal benefit for air quality improvement options using choice experimental design: evidence from Klang Valley, Malaysia - Sarabdeen, Masahina; Bedawi ELFadli ELmonshid, Lena; Rafia, Afroz; Muhammadu Kijas, Abdul Cafoor; Adam, Shehu Usman (Journal of Critical Reviews, 2020)
This study aimed to estimate willingness to pay of households for air quality improvement and marginal benefits that household derived from the improved air- quality management plan in Klang Valley, Malaysia. A choice experiment study was administered to 300 households and the data was analysed using the multinomial logit model. It was found that number of sick days, air pollution index, medical expenditure, outdoor activities, ethnic, city, age, and respiratory symptoms are significant variables, which affected the willingness to pay of the respondents in Klang Valley. The mean willingness to pay for the new air quality management programme derived from choice experiment multinomial logit model is MYR1.99 per litre of fuel, consumer-compensating surplus is 0.04 and estimated marginal benefit is 1.83. The results reveal that households are willing to pay significant amounts in terms of higher fuel price to ensure the air quality improvement and reduce environmental and health risks in Malaysia. Hence, this study would help to produce multiple policies and recommendations to improve the air quality. It is also possible to develop efficient and equitable motor vehicle rules and promote technology advancement in this area. Effective measures in managing and planning city development should be emphasised to reduce vehicle travel and congestion, travel time, traffic jam and pollutant emissions in Klang Valley metropolitan region.